2004
DOI: 10.1653/0015-4040(2004)087[0176:iaefnt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate Animals Extracted From Native Tillandsia (Bromeliales: Bromeliaceae) in Sarasota County, Florida

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 4 publications
3
37
0
11
Order By: Relevance
“…On the other hand, phytotelmata communities are important as small repositories or refuges of biodiversity, particularly in habitats undergoing great changes (Armbruster et al, 2002;Noss, 1990), and also take part in forest maintenance by redistributing nutrients to the soil, as epiphytic bromeliads and their communities process nutrients before falling to the ground from the canopy. Frank et al (2004) warns the investigators that wish to work in the Neotropical region that they will encounter severe taxonomic problems. The effort to collect the specimens is small compared with the effort required to identify the specimens reliably to the species level.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, phytotelmata communities are important as small repositories or refuges of biodiversity, particularly in habitats undergoing great changes (Armbruster et al, 2002;Noss, 1990), and also take part in forest maintenance by redistributing nutrients to the soil, as epiphytic bromeliads and their communities process nutrients before falling to the ground from the canopy. Frank et al (2004) warns the investigators that wish to work in the Neotropical region that they will encounter severe taxonomic problems. The effort to collect the specimens is small compared with the effort required to identify the specimens reliably to the species level.…”
Section: Introductionmentioning
confidence: 99%
“…Few species of Psychodidae have been collected in bromeliads. Frank et al (2004) studied the Diptera fauna associated with bromeliads in Florida and reported 190 larvae and pupae of Alepia Enderlein, 1937, but did not provide specific identifications. Knab (1914) described three species: Philosepedon fumata (Knab, 1914) from Mexico; Neurosystasis amplipenna (Knab, 1914) from Cuba; and Alepia tricolor (Knab, 1914) Wagner et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Estudios con diferentes especies de bromeliáceas en los géneros Aechmea, Guzmania, Hohenbergia, Tillandsia y Vriesea, han señalado que dentro de los organismos asociados a estas fi totelmatas, la Clase Insecta presenta la mayor abundancia y diversidad (Ingunza 1995;Greeney 2001;Mestre et al 2001;Frank et al 2004;Ospina-Batista et al 2004). …”
Section: Invertebrados Totalesunclassified